Older adults compensate for switch, but not mixing costs, relative to younger adults on an intrinsically cued task switching experiment - Eich, Teal S.; Langfield, Christopher; Sakhardande, Jayant; Gazes, Yunglin; Habeck, Christian; Stern, Yaakov (Frontiers in Aging Neuroscience, 2023)
Introduction Aging negatively impacts the ability to rapidly and successfully switch between two or more tasks that have different rules or objectives. However, previous work has shown that the context impacts the extent of this age-related impairment: while there is relative age-related invariance when participants must rapidly switch back and forth between two simple tasks (often called “switch costs”), age-related differences emerge when the contexts changes from one in which only one task must be performed to one in which multiple tasks must be performed, but a trial-level switch is not required (e.g., task repeat trials within dual task blocks, often called “mixing costs”). Here, we explored these two kinds of costs behaviorally, and also investigated the neural correlates of these effects. Methods Seventy-one younger adults and 175 older adults completed a task-switching experiment while they underwent fMRI brain imaging. We investigated the impact of age on behavioral performance and neural activity considering two types of potential costs: switch costs (dual-task switch trials minus dual-task non-switch trials), and mixing costs (dual-task non-switch minus single-task trials). Results We replicated previous behavioral findings, with greater age associated with mixing, but not switch costs. Neurally, we found age-related compensatory activations for switch costs in the dorsal lateral prefrontal cortex, pars opercularis, superior temporal gyrus, and the posterior and anterior cingulate, but age-related under recruitment for mixing costs in fronto-parietal areas including the supramarginal gyrus and pre and supplemental motor areas. Discussion These results suggest an age-based dissociation between executive components that contribute to task switching.